Малява с воли: роман / И. В. Агафонов - Агафонов Игорь В. (Бандитский роман, 2002)
Экземпляры: ф.5 (2003) / Инвентарный номер: 47401 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 23 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-4